EVALUASI JARINGAN INTERNET PADA PERGURUAN TINGGI SWASTA DI KOTA PALEMBANG - Purwanto, Timur Dali ; Irwansyah, Irwansyah (JURNAL ILMIAH MATRIK, 2017)
The use of Internet technologies in education is part of the concept of educational technology in the form of media to facilitate teaching and learning process. In this research will focus only on the Internet network of research universities in the Municipality of Palembang. By applying the method of QOS (Quality of Service) to determine a number of factors or parameters that affect the quality of the Internet network through wired and wireless media in higher education sekotamadya Palembang. The QOS parameters is composed of bandwidth, throughput, delay, jitter and packet loss. The analytical tool used in this study using statistical software Biznet Speed Meter and Axence Net Tools. The results of measurements of QOS parameters will be compared with a standard internet network quality measurement standard of TIPHON version. From the measurement results is intended to determine the quality of the computer network at the private College in Palembang. Keywords: QoS (Quality of Service), Internet, Cable, Wireless